Investigation into the influence of macro-scale geometry on the stability of underground excavations in layered rock masses. Issue 1 (August 2021) - Ingham, J; Vazaios, I; Paraskevopoulou, C
Abstract: Underground excavations for the development of infrastructure, mining operations, waste management etc. require support measures to ensure stability both during their construction and operational phases, which highly depends on the rock mass strength and deformability. Discontinuities within the rock mass are intrinsic features which determine said strength and deformability and affect the excavation stability. Several defining parameters demonstrate that rock mass variability has significant control in the material response during an excavation, especially in sedimentary rocks. In this paper, the Thornhill Sandstone is examined by applying numerical analysis and its mechanical response is investigated under several scenarios with varying excavation geometries, stress conditions while incorporating the influence of discontinuities explicitly within the numerical model. A two-dimensional parametric analysis is performed by applying the Finite Element Method (FEM) and integrating Discrete Fracture Networks (DFNs). More specifically, four different excavation geometries and three different in situ stress regimes are investigated. Drawing on the results, this paper provides insights for tunnel design optimisation when layered rock masses are encountered during an excavation in various underground stress environments with different opening geometries.